Gambaran Karakteristik dan Kepuasan Peserta BPJS Kesehatan dalam Pemanfaatan Pelayanan Kesehatan di FKTP Kota Malang - Febri Endra Budi Setyawan (Puslitbang Sinergis Asa Professional, 2020)
The rules regarding the increase in Social Insurance Administration Organization (BPJS) Health fees recently affected the occurrence of 800 thousand BPJS Health participants who dropped out of class. The level of satisfaction of BPJS Health participants utilizing health services at the First Level Health Facilities (FKTP) was still below the target. The satisfaction of the participants of the BPJS of Health when getting health services in FKTP will have a strong influence on their loyalty and the quality of health services in general. This study conducted to describe the characteristics and satisfaction of BPJS Health participants in the utilization of health services in FKTP Malang. This study wass a descriptive study an observational survey approach to describe the characteristics and satisfaction of BPJS Health participants. This study involved 49 BPJS participants in FKTP Malang at the Primary Care Clinic and Community Health Center by using systematic random sampling. Results: The results showed that in both types of FKTP groups, 100% of participants stated that they preserved their chosen health services. All participants of the Subsidy Aid Recipient (PBI) checked their health at the Community Health Center, while at the primary care clinic, the majority of participants (75%) were Wage Recipient Workers (PPU). The level of satisfaction of BPJS participants in primary care clinic was more dominated by biological aspects (84.85%), while psychological aspects were more felt by participants in Community Health Center. In conclusion, The conclusion of this study shows that PBI participants checks their health more at Community Health Center and they felt more satisfy on biological aspects at Primary Care Clinic. BPJS Health participants' satisfaction in both FKTP groups needs to be improved through a comprehensive holistic approach with promotive, preventive, curative and rehabilitative efforts.